2022
DOI: 10.1101/2022.06.10.22276249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiographic Assessment of Lung Edema (RALE) Scores are Highly Reproducible and Prognostic of Clinical Outcomes for Inpatients with COVID-19

Abstract: INTRODUCTION: Chest imaging is necessary for diagnosis of COVID-19 pneumonia, but current risk stratification tools do not consider radiographic severity. We quantified radiographic heterogeneity among inpatients with COVID-19 with the Radiographic Assessment of Lung Edema (RALE) score on Chest X-rays (CXRs). METHODS: We performed independent RALE scoring by ≥2 reviewers on baseline CXRs from 425 inpatients with COVID-19 (discovery dataset), we recorded clinical variables and outcomes, and measured plasma ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(34 reference statements)
2
8
0
Order By: Relevance
“…In subgroups of ARDS patients, we did not find associations between ARDS subgroups and our primary outcome, 30-day mortality, but did find an association between the baseline RALE score and 90-day mortality in non-COVID-ARDS patients only. These conflicting results are in line with previous literature, as most studies found no associations [ 8 , 9 , 10 , 11 ], whereas the original [ 5 ] and another study [ 7 ] did find an association between baseline RALE scores and mortality in ARDS patients. These inconsistent findings in ARDS studies might be caused by the heterogeneous ARDS population, the different inclusion and exclusion criteria or the timing of the CXRs [ 5 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In subgroups of ARDS patients, we did not find associations between ARDS subgroups and our primary outcome, 30-day mortality, but did find an association between the baseline RALE score and 90-day mortality in non-COVID-ARDS patients only. These conflicting results are in line with previous literature, as most studies found no associations [ 8 , 9 , 10 , 11 ], whereas the original [ 5 ] and another study [ 7 ] did find an association between baseline RALE scores and mortality in ARDS patients. These inconsistent findings in ARDS studies might be caused by the heterogeneous ARDS population, the different inclusion and exclusion criteria or the timing of the CXRs [ 5 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Discussionsupporting
confidence: 77%
“…Pulmonary edema typically results in ventilation-perfusion mismatch, and subsequent hypoxemia may require ventilation with higher pressures due to decreased compliance of the lung [ 1 ]. At hospital presentation, baseline RALE scores demonstrated an association with ICU admission and mortality [ 11 , 12 , 13 , 14 , 15 ]. In the ICU, ARDS patients with higher baseline RALE scores, indicating more radiographic lung edema, were found to have a higher mortality in one study [ 5 ], although other studies found stronger associations between the change in RALE score and mortality [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 Our study focused on using CSS, a simple and reliable scoring system when compared to other widely studied scoring systems like Radiographic assessment of lung edema (RALE/modified RALE) and Brixia. 27. , 28.…”
Section: Discussionmentioning
confidence: 99%
“…b. The COVID INpatient Cohort (COVID-INC) enrolled moderately ill inpatients with COVID-19 hospitalized in dedicated inpatient wards [11].…”
Section: Clinical Cohortsmentioning
confidence: 99%